Międzynarodowa pozycja konkurencyjna w świetle rozwoju technologii teleinformatycznych - Gryczka, Marcin (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The goal of this paper is to analyse the changing role of information and communication technologies (ICTs) and to determine their influence on selected countries' international competitiveness. To achieve this, the calculated global ICT development index has been compared to selected measures of international competitive position. Conducted research has confirmed that in respect of ICT a partial alignmentbetween developed and other countries has occurred. Moreover, there is a noticeable interdependence between ICT development and international competitive position indicators.